Kudüs Tasarısı Oylaması ve Türkiye’nin Ortadoğu’daki İmajı / Voting of Jerusalem Proposal and Turkey’s Image in the Middle East - Pınar, Latif (Journal of History Culture and Art Research, 2018)
Abstract On December 6th, 2017, The United States President Donald Trump declared that the USA had unilaterally accepted Jerusalem as the capital of Israel and that he had instructed the Ministry of Foreign Affairs to move the US Embassy in Tel Aviv to Jerusalem. Right after this declaration under the leadership of Turkey a draft resolution containing criticism of the president Trump and matters related to determining the status of Jerusalem was prepared and submitted to the United Nations General Assembly for voting. This resolution proposal, titled as "Israel’s Activities in East Jerusalem and Palestinian Territory under Occupation", was voted at a special session of the United Nations General Assembly on December 21st, 2017 and was adopted on the basis of 128 admission, 9 rejection and 35 noncommittal votes. The aim of this study is to examine the impact of the voting carried out in the United Nations General Assembly on the image of Turkey in the Middle East. Öz 6 Aralık 2017’de Amerika Birleşik Devletleri Başkanı Donald Trump, Kudüs’ü tek taraflı bir şekilde İsrail’in başkenti olarak kabul ettiğine ve Tel Aviv’de bulunan Amerikan Büyükelçiliği’nin Kudüs’e taşınması için Dış İşleri Bakanlığı’na talimat verdiğine yönelik bir açıklama yapmıştır. Bu açıklamanın hemen ardından Türkiye’nin öncülüğünde, Başkan Trump’ın kararının eleştirilmesi ve Kudüs’ün statüsünün belirlenmesine ilişkin bir takım hususları içeren bir karar tasarısı hazırlanmış ve oylanmak üzere Birleşmiş Milletler Genel Kurulu’na sunulmuştur. İsrail’in İşgal Altındaki Doğu Kudüs ve Filistin Topraklarındaki Faaliyetleri başlıklı bu karar tasarısı, 21 Aralık 2017’de Birleşmiş Milletler Genel Kurulu’nda gerçekleştirilen bir özel oturumda oylamaya sunulmuş ve 128 kabul, 9 ret ve 35 çekimser oy neticesinde kabul edilmiştir. Bu çalışma, Birleşmiş Milletler Genel Kurulu’nda gerçekleştirilen söz konusu oylamanın Türkiye’nin Ortadoğu’daki imajına olan etkisini incelemeyi amaçlamaktadır.